Optimized Distributed Control for Power Sharing and Voltage-Frequency Regulation in Islanded Microgrids - Neethu Sajeev; Stephen Arinze Obi; Jae-Jung Jung (IEEE Access)
This study examines the interactions among multiple distributed generators in an islanded microgrid with predominantly resistive line impedances. The primary objective is to ensure stable frequency and voltage regulation under disturbances, such as load changes while achieving accurate power sharing. A multiagent distributed control system, based on a hierarchical control structure, is implemented to facilitate the seamless integration of energy resources into the microgrid. The proposed hierarchical control framework consists of Finite Control Set Model Predictive Control (FCS-MPC)-based zero-level control, inverse droop-based primary control, and a finite-time optimal distributed secondary controller (SC). The FCS-MPC ensures precise voltage and current regulation by generating optimal switching pulses for each distributed generator (DG), thereby improving power delivery accuracy. Inverse droop control effectively decouples active and reactive power in resistive-dominant lines, ensuring proper load sharing. The secondary controller restores voltage and frequency with finite-time convergence, enhancing overall system stability. A dedicated communication network enables real-time coordination among the DGs, ensuring efficient operation under varying grid conditions. The proposed distributed secondary control is assessed by incorporating FCS-MPC-based inner control. Controller hardware in the loop (C-HIL) experimental tests are conducted with three DGs having different line impedances and local loads. The results validate the controller’s performance in voltage and frequency restoration and power sharing.